2007
DOI: 10.1111/j.1469-8749.2007.00621.x
|View full text |Cite
|
Sign up to set email alerts
|

Sedation with 50% nitrous oxide/oxygen for outpatient dental treatment in individuals with intellectual disability

Abstract: Persons with intellectual disability have difficulty in cooperating with outpatient care, and many are referred for general anaesthesia. Intellectual disability has traditionally been a contraindication for conscious sedation. We evaluated the behavioural impact, effectiveness, and tolerance of sedation in this population using a fixed 50% nitrous oxide/oxygen mixture as a single agent. We used dental treatment as a model of outpatient care; 349 patients (192 males, 157 females; mean age 22y [SD 14]; range 3-8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 21 publications
3
29
0
4
Order By: Relevance
“…Faulks et al (30) reported that sedation with 50% N 2 O/O 2 for outpatient dental treatment of patients with intellectual disability was safe and effective; during 605 sedation sessions no serious side effects were observed and minor side effects (such as nausea, vomiting, sweating, headache) occurred in 10.1% of the sessions. In terms of a 10-year retrospective study, it has been reported that the use of N 2 O/O 2 sedation provides reliable conscious sedation in the pediatric outpatient population; the nausea and vomiting rate was 1.5% (4).…”
Section: Discussionmentioning
confidence: 99%
“…Faulks et al (30) reported that sedation with 50% N 2 O/O 2 for outpatient dental treatment of patients with intellectual disability was safe and effective; during 605 sedation sessions no serious side effects were observed and minor side effects (such as nausea, vomiting, sweating, headache) occurred in 10.1% of the sessions. In terms of a 10-year retrospective study, it has been reported that the use of N 2 O/O 2 sedation provides reliable conscious sedation in the pediatric outpatient population; the nausea and vomiting rate was 1.5% (4).…”
Section: Discussionmentioning
confidence: 99%
“…Bu hasta grubunda hem genel anestezi hemde sedasyon uygulamaları sıklıkla uygulanabilmektedir [5,[10][11][12]. Genel anestezi ağırlıklı olarak uygulanmasına rağmen diş tedavisi için %50 N2O/O2 sedasyonun bile %91.4 oranında başarılı olduğu da belirtilmiştir [13]. Buna rağmen hastaları sedasyon düzeyini derinleştirmeden operasyon koltuğunda tutmak çoğu zaman imkansız olabilmektedir.…”
Section: Discussionunclassified
“…Çoğu zamanda midazolamın antikonvülzan özelliğinden faydalanmak için kombine şekilde kullanıyoruz. Literatürde de diş hekimliğinde bu hasta grubunda farklı anestezik ajanlar kullanılmıştır [4,5,10,12,13,17]. Benzodiazepinler, narkotik ajanlar ve propofol intravenöz sedasyon için sıklıkla kullanılmaktadır.…”
Section: Discussionunclassified
“…20 Nitröz oksit/oksijen sedasyonunun etkin olduğu alanlardan biri de zihinsel yetersizliği olan hastalardır. Faulks ve arkadaşları 5 2007 yılında yayınlanan çalışma-da, entellektüel yetersizliği olan bireylerde diş hekimliği tedavilerini %50 konsantrasyonda nitröz oksit/oksisijen kombinasyonu ile gerçekleştirmiştir. Yazarlar araştırma sonuçlarına göre işlemlerin %91.4'ünün başa-rılı olduğunu, hiçbir ciddi yan etki gelişmediğini, minor yan etki oranının ise %10.4 olduğunu bildirmişlerdir.…”
Section: Nitröz Oksit/oksijen Sedasyonunun Avantajları Ve Dezavantajlarıunclassified
“…1,6,9,14 Nitröz oksit/oksijen sedasyonu esnasında oluĢabilecek komplikasyonlar Nitröz oksit/oksijen sedasyonu tekniğe uygun bir şekilde gerçekleştirildiğinde az sayıda komplikasyon gelişmektedir. 5,9,23,24 Davranış problemleri, bulantı, tükürük ve ter salgısında artış, titreme gibi istenmeyen yan etkilerin çoğu nitröz oksidin titrasyon yapılmadan iletimine ve yüksek dozlarda uygulanmasına bağlı olup, işlem esnasında nitröz oksit konsantrasyonunun %5-10 oranında düşürülmesiyle ortadan kaldırılabilmekte-dir. 14 Bununla birlikte kusma, halüsinasyon oluşumu, şiddetli ajitasyon, bilincin kapanması gibi daha ciddi komplikasyonların gelişmesi halinde derhal nitröz oksit akışı kesilerek gerekli tedavi uygulamasının sağlanması gerekmektedir.…”
Section: Hasta Monitörizasyonuunclassified